2020
DOI: 10.7860/jcdr/2020/44743.14049
|View full text |Cite
|
Sign up to set email alerts
|

Utility of TP53 in Breast Carcinoma Immunophenotypes

Abstract: Breast cancer is a heterogeneous disease and has significant variability in presentation, treatment response, and prognosis. The management of carcinoma breast is currently based on immunophenotypes and Tumour Nodes Metastasis (TNM) staging. The aim of the study is to review the literature and to look for treatment guidelines of carcinoma breast, the role of immunophenotypes in treatment of carcinoma breast, TP53 mutation in breast cancer, and the relationship of TP53 mutation with immunophenotypes, histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to the diagnosis, the patient got medical treatment in an emergency situation, and the patient life was secure. [5][6][7][8][9][10][11] According to the literature that is now accessible, the incidence of tumours typically ranges from 0.7 percent to 11.7 percent, but in recent years, a progressive rise has been noticed, which may be attributed to the ageing population and developments in medical technology and equipment.12-20 According to estimates, 10% of cancer survivors in the US received at least one new primary cancer diagnosis between 1973 and 2000; this percentage has been increasing recently. In terms of the number of primary malignant tumours, MPM with two types of main malignant tumours is typical, whereas MPM with three or fewer types of primary malignant tumours is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…According to the diagnosis, the patient got medical treatment in an emergency situation, and the patient life was secure. [5][6][7][8][9][10][11] According to the literature that is now accessible, the incidence of tumours typically ranges from 0.7 percent to 11.7 percent, but in recent years, a progressive rise has been noticed, which may be attributed to the ageing population and developments in medical technology and equipment.12-20 According to estimates, 10% of cancer survivors in the US received at least one new primary cancer diagnosis between 1973 and 2000; this percentage has been increasing recently. In terms of the number of primary malignant tumours, MPM with two types of main malignant tumours is typical, whereas MPM with three or fewer types of primary malignant tumours is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…al. focussed on utility of TP53 in breast carcinoma immunophenotypes [15]. Related studies by Laddha et.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that spectral color doppler is a reliable technique in predicting malignancy of BI-RADS 3 breast masses. Few of the related studies on breast malignancies were reviewed [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%